Maternal Gestational Diabetes Associated with Higher Child BMI Z-Score at Preschool and Lower Likelihood of Breastfeeding Initiation - Mosli, Rana H.; Al-Lahyani, Manal N.; Najjar, Amani; Zoghbi, Doaa A.; Al-Haddad, Rawan H.; Mosli, Hala H. (International Journal of Child Health and Nutrition, 2018)
Objectives: To examine the association of maternal GDM with 1) child BMI z-score at preschool; 2) breastfeeding initiation and duration, while adjusting for child birthweight in addition to potential confounders. Method: Sample included 53 children (3 - 5 years old) recruited from two preschools in Jeddah, Saudi Arabia. Mothers completed a self-administered questionnaire. Child anthropometry was completed using standardized procedures. BMI z-scores were calculated using the WHO standards/reference data. Linear regression models were tested to examine the association between maternal GDM and child BMI z-score, as well as breastfeeding duration. Logistic regression models were tested to examine the association between maternal GDM and breastfeeding initiation. Models were adjusted for child birthweight, maternal BMI, and maternal age at pregnancy. Results: Mean child BMI z-score was 1.10 (SD= 1.22). About one quarter (24.5%) of mothers reported being diagnosed with GDM. Mean birthweight of children whose mothers were diagnosed with GDM was 3.10 kg (SD= 0.74). Adjusting for covariates, we found that maternal GDM was associated with increased child BMI z-score (B= 1.04, 95% CI= 0.14 - 1.94, P-value= 0.02), and lower odds of breastfeeding initiation (OR= 0.10, 95% CI= 0.02 – 0.49, P-value= 0.005). Maternal GDM was not associated with breastfeeding duration (B= -4.75, 95% CI: -11.79 – 2.29, P-value= 0.18). Conclusion: Findings suggest that maternal GDM is associated with higher child BMI z-score at preschool and lower likelihood of breastfeeding initiation. Studies are needed in order to identify the underlying mechanisms of associations. Obesity prevention programs may target children whose mothers were diagnosed with GDM; prenatal breastfeeding counseling may be offered.